Students’ Humility and Implication in Counseling Services: A Systematic Literature Review - Rohmatus Naini; Mungin Eddy Wibowo; Edy Purwanto; Mulawarman Mulawarman (Universitas Negeri Semarang, 2022)
Character education is an important part to be improved by school counselors through guidance and counseling services. One of the virtues that forms the basis for the development of other virtues is humility. Individuals who have high humility will be humble, kind, forgiving, and have high prosociality, on the other hand, individuals with low humility tend to be arrogant, arrogant, narcissistic and powerful so they are prone to conflict between friends. This study describes the humble character of students and their implications for counseling services. This systematic literature review begins with formulating research questions, objectives, compiling inclusion and exclusion criteria, searching for articles through databases, analyzing and reporting. Article search results are sorted and inputted in a prism diagram which is then presented per articleThe intellectual development of humility is used as a preventive effort in managing conflict and increasing many strengths such as gratitude, kindness, self-compassion, forgiveness, responsibility, discipline, integrity, and other good characters. Implications and suggestions for further research are described in this article.